The Role of Informed Consent as Legal Protection for Doctors in Conducting Medical Procedures - Fitriana, Dian (Sinergi International Journal of Law, 2023)
The field of Health Law recognizes Therapeutic Transactions as an agreement between a doctor and a patient, granting authority to the doctor to provide healthcare services to the patient based on their expertise and skills. Therapeutic transactions take the form of informed consent or approval of medical procedures before they are carried out. Informed consent involves the doctor explaining to the patient the condition of their illness and the medical procedures intended to address it, in the doctor's efforts to achieve recovery. Research findings indicate that informed consent plays a crucial role in the relationship between doctors and patients, serving as written evidence of the agreement between the doctor and the patient before medical procedures are undertaken. Informed consent can serve as the basis for proving whether a patient accepts or refuses a medical procedure, providing protection to the doctor. Legal protection for doctors is obtained as long as they carry out procedures in accordance with professional standards and operational procedures. For doctors, informed consent provides a sense of security when performing medical procedures on patients and can be used as a means of self-defense against potential claims or lawsuits from patients or their families if the medical procedure results in unintended consequences. Legal measures that doctors can take in the event of an undesired outcome related to medical procedures include attempting mediation with the patient first. If mediation fails or lacks good faith, the resolution may proceed through the legal system.